Strategi Program Pemberdayaan Usaha Peningkatan Pendapatan Keluarga (UP2K) dalam Meningkatkan Kesejahteraan Ekonomi Masyarakat di Kelurahan Sukaluyu Kota Bandung: Penelitian - Sri Damayanti; Raihannisa Fadilla Nazla Nugraha; Pungki Nurlatifah; Rahma Gina Amelia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the strategy of the Family Income Improvement Business (UP2K) empowerment program in Sukaluyu Village, Cibeunying Kaler District, Bandung City, and to find out what obstacles are faced in the UP2K empowerment program in improving the economic welfare of the community in Sukaluyu Village. The method in this research uses descriptive qualitative research methods. The results of the study show that the UP2K strategy in improving economic welfare in Sukaluyu Village, Cibeunying Kaler District, Bandung City includes conducting skills training, coaching, mentoring, and lending capital in opening or developing a business. Meanwhile, obstacles faced in the UP2K empowerment program in Sukaluyu Village such as budget problems, community businesses that experience congestion and unevenness, a lot of competition, lack of management, late return of capital, and misuse of capital loans.